The Influence of Online Shopping Through Shopee, Lifestyle and Financial Literacy on the Consumptive Behavior of Gunung Rinjani University Students - Della Hastiana; Sulkiah Sulkiah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The rapid development of digital technology has profoundly transformed consumption patterns in society, particularly among students. The convenience of online shopping through e-commerce platforms such as Shopee, combined with modern lifestyle trends and low levels of financial literacy, often fosters consumptive behavior. This tendency is evident in habits of excessive purchasing, decisions driven more by desire than necessity, and the urge to follow prevailing trends. Such behavior not only affects daily life but also influences students’ financial management, especially for those who depend on parental financial support. This study aims to empirically analyze the influence of online shopping through Shopee, lifestyle, and financial literacy on students’ consumptive behavior at Universitas Gunung Rinjani. Employing a quantitative method with an associative approach, the research involved 55 students selected through purposive sampling based on specific criteria. Data were collected via questionnaires using a Likert scale and analyzed through validity and reliability tests, classical assumption tests, and multiple linear regression using SPSS software. The findings reveal that: (1) online shopping through Shopee positively and significantly affects students’ consumptive behavior; (2) lifestyle has a positive impact on consumptive tendencies; (3) financial literacy exerts a significant negative effect on consumptive behavior; and (4) jointly, these three variables significantly influence students’ consumptive behavior. In conclusion, the ease of transactions on Shopee, a hedonistic lifestyle orientation, and varying levels of financial literacy collectively shape students’ consumptive patterns. Therefore, enhancing financial literacy, regulating e-commerce usage, and promoting a more modest lifestyle are recommended to mitigate excessive consumption.